What is the most efficacious initial treatment for adults with localized psoriatic lesions?. Issue 11 (November 2015) - Caylor, Tonya; Waldman, Leslie
Abstract : Evidence‐Based Answer : Topical treatments with vitamin D preparations or corticosteroids are the first‐line intervention for localized (<10% of body surface area) psoriatic lesions. Combination therapy is superior in efficacy to monotherapy with either treatment alone (SOR: A, systematic review of RCTs and an evidence based guideline).